The different surgical impact of the superior cavoatrial incision in children and adults. (15th May 2021) - Ait-Ali, Lamia; Ravaglioli, Antonio; Festa, Pierluigi; Tamburrini, Alessandro; Marrone, Chiara; Cuman, Magdalena; Farnetani, Cecilia; Pak, Vitali; Chiavarelli, Mario; Federici, Duccio
Abstract: Introduction: The single- and double-patch repairs are undoubtedly the most commonly used techniques for the surgical management of partial anomalous pulmonary venous connection associated with sinus venosus atrial septal defect. The aim of this study was to retrospectively compare early and long-term surgical outcomes in paediatric and adult patients, focusing in particular on the occurrence of ectopic atrial rhythm. Material and methods: Seventy patients (male: 38, 54.2%) underwent surgical repair for partial anomalous pulmonary venous connection with sinus venosus atrial septal defect. Forty-nine patients (70%) underwent surgical repair in paediatric age (<16 years old), while 21 of (30%) patients were operated in adulthood. Thirty patients (42.8%) underwent single-patch repair and 39 patients (55.7%) underwent double-patch repair. In only one patient, the Warden procedure was performed (1.4%). Median follow-up time was 52 months (IQ 15.1–113). Results: The type of surgical technique didn't affect the incidence of ectopic atrial rhythm (26.6% in single-patch group and 25.6% in double-patch groups, p = 0.9). At long-term follow-up, ectopic atrial rhythm, as an expression of sinoatrial node disturbance, was however significantly more frequent in the paediatric population (28.8% paediatric group and 4.7% adult group, p = 0.02). Conclusions: The higher incidence of ectopic atrial rhythm in children is probably related to the closer position of the sinus node to the superior cavoatrial incision, which makes irreversible iatrogenic traumatism more likely to occur. Surgical techniques that avoid any manipulation on the superior cavoatrial junction should, therefore, be preferred for children undergoing partial anomalous pulmonary venous connection repair.